World Population Policies 2015 - United Nations Department of Economic; Social Affairs (United Nations, 2019)
This report provides a comprehensive overview of key aspects of population policies and dynamics for 197 countries since the mid-1970s. Updated biennially, it documents changes in key aspects of Government views and policies related to population size and growth, population age structure, fertility, reproductive health and family planning, health and mortality, spatial distribution and internal migration, and international migration. The report also includes two-page country profiles, with the first page containing information on changes in the Government views and policies and the second page containing data on selected population indicators corresponding to 1985, 1995, 2005, 2013 and 2015, the most recent revision year.